2023
DOI: 10.3389/fendo.2023.1155925
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity in infancy and early childhood: a narrative review of interventions for prevention of obesity and associated health outcomes

Natalie Eichner-Seitz,
Russell R. Pate,
Ian M. Paul

Abstract: In the context of the childhood obesity epidemic, this narrative review aims to explore opportunities to promote physical activity (PA) between birth and age 5 years as well as the health outcomes associated with PA in early childhood. Although early childhood is an ideal time to promote healthy habits, guidelines for PA have often ignored early childhood given the limited evidence for children <5 years old. Herein we discuss and highlight infant, toddler and preschool age interventions to promote PA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 131 publications
(184 reference statements)
0
3
0
Order By: Relevance
“…We reasoned that using C/H detection in the preprocessing phase of the automated MAIJU analysis pipeline would improve focusing on time periods when the infants are moving by themselves. The same need to distinguish a child’s own activity from other physical movements is clear in studies that aim to understand developmental origins of childhood obesity and related health adversities 34 . Second, there are also many other comparable needs in infant behavioral research where unsupervised measurement sessions need to be segmented for movement periods by the infant versus by an external force 13 , 16 .…”
Section: Discussionmentioning
confidence: 99%
“…We reasoned that using C/H detection in the preprocessing phase of the automated MAIJU analysis pipeline would improve focusing on time periods when the infants are moving by themselves. The same need to distinguish a child’s own activity from other physical movements is clear in studies that aim to understand developmental origins of childhood obesity and related health adversities 34 . Second, there are also many other comparable needs in infant behavioral research where unsupervised measurement sessions need to be segmented for movement periods by the infant versus by an external force 13 , 16 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the timing of when this sex gap begins is yet unclear as PA development at infancy and toddler ages has only recently begun to be investigated. 10 Among the few existing studies, while an infant study reported no sex differences in PA, 11 some toddler studies, 12 but not all, 13,14 found signi cant sex differences in PA. Taken together, the sex gap in PA may begin to emerge in late infancy or early toddler ages.…”
Section: Introductionmentioning
confidence: 99%
“…School closures, alteration in daily activities, and the loss of structure and control were adversely related with children obesity concerning the COVID-19 confinement period [ 29 , 30 ]. There is also substantial evidence that physical activity between childbirth and the age of 5 years old may further prevent obesity both in the short and long-term [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%